An interpretation of the economic theory of fertility: promising path or blind alley? - Leibenstein, Harvey (Journal of Economic Literature, 1974)
Some economists are doing research in applying Hicksian microtheory to explain the fertility behavior of man and fertility differentials. This article considers some highlights of the problem to serve for further reading. In reviewing the recent economic sociological and population theories there are 1) the theory of demographic transition which depends heavily on the reduction of desired fertility 2) Leibensteins 1957 theory of fertility which addressed itself primarily to the question and explanation of fertility decline in the course of sustained per capita income growth 3) the Chicago School theories among which is Beckers theory which applied the Hicksian version of microconsumption theory to family fertility behavior and came up with some interesting interpretations and 4) other theories which emphasize infant mortality effects socioeconomic status changes in norms and institutions threshold values in income and/or education etc. The author places more emphasis on the critique and methodological analysis of the Chicago School theories and finally turns toward the discussion of a possibly more adequate theory which assumes that there is a higher degree of substitution between the extent to which people indulge themselves in causual decision making and the point at which economic constraints force or create strong pressures for calculated decision making.